Pengaruh Kecerdasaan Emosional, Job Competence, Dan Kompetensi Komunikasi Terhadap Kepemimpinan Kolaboratif Pada PT. Perkebunan Nusantara IV Regional III Kebun Tandun Riau - Olivia Maghdalena Br Simamora; Elperida Juniarni Sinurat; Kristanty M.N Nadapdap (CV. Ulil Albab Corp, 2026)
The purpose of this study is to examine the effect of Emotional Intelligence, Job Competence, and Communication Competence on Collaborative Leadership at PT Perkebunan Nusantara IV Regional III, Tandun Plantation, Riau. The population of this study consisted of all leaders working at PT Perkebunan Nusantara IV Regional III, Tandun Plantation, Riau. This study employed a non-probability sampling method. The non-probability sampling technique used was saturated sampling, meaning that all members of the population were used as the sample, totaling 76 respondents. The data analysis techniques used were statistical tests including regression analysis, t-test, Moderated Regression Analysis (MRA), and the coefficient of determination (R-Square). The results of this study indicate that emotional intelligence has a partial and significant effect on collaborative leadership at PT Perkebunan Nusantara IV, Tandun Plantation, Riau. Job Competence also has a partial and significant effect on collaborative leadership at PT Perkebunan Nusantara IV, Tandun Plantation, Riau. Communication competence likewise has a partial and significant effect on collaborative leadership at PT Perkebunan Nusantara IV, Tandun Plantation, Riau. Based on the coefficient of determination analysis, the adjusted R-Square value obtained was 0.615 or 61%, indicating that emotional intelligence, Job Competence, and communication competence contribute 61% to collaborative leadership at PT Perkebunan Nusantara IV Regional III, Tandun Plantation, Riau, while the remaining 39% is influenced by other variables or factors not examined in this study.